INTEGRATING THEORY AND PRACTICE: AN EDUCATIONAL CHALLENGE - B. Ott (Acta Theologica)
As an introduction to this volume on the theme “Integrating theory and practice: An educational challenge”, this article unfolds various aspects of the relationship between and the integration of theory and practice. In conversation with Paulo Freire, Clemens Sedmak, Thomas Groome, as well as John Biggs and Catherine Tang, pertinent issues in relation to “theory” and “practice/praxis” are explored. This is done in the form of fictive conversations with research students and self-critical reflections of a supervisor. The article emphasises the embodied integration of theory and practice in the lives of theological researchers, teachers and supervisors. With this, the article intends to set the agenda for the Supplementum and provoke inspiring conversations.